Nose Structure Delineation of Bouguer Anomaly as the Interpretation Basis of Probable Hydrocarbon Traps: A Case Study on the Mainland Area of Northwest Java Basin - Kamtono Kamtono; D. D. Wardhana (Indonesian Journal on Geoscience, 2012)
DOI: 10.17014/ijog.v7i3.144Two important aspects in the exploration of oil and gas are technology and exploration concepts, but the use of technology is not always suitable for areas with geological conditions covered by young volcanic sediments or limestone. The land of the Northwest Java Basin is mostly covered by young volcanic products, so exploration using seismic methods will produce less clear image resolution. To identify and interpret the subsurface structure and the possibility of hydrocarbon trap, gravity measurements have been carried out. Delineation of nose structures of a Bouguer anomaly map was used to interpret the probability of hydrocarbon traps. The result of the study shows that the gravity anomalies could be categorized into three groups : low anomaly (< 34 mgal), middle anomaly (34 - 50 mgal), and high anomaly (> 50 mgal). The analysis of Bouguer anomaly indicates that the low anomaly is concentrated in Cibarusa area as a southern part of Ciputat Subbasin, and in Cikampek area. The result of delineation of the Bouguer anomaly map shows the nose structures existing on Cibinong-Cileungsi and Pangkalan-Bekasi Highs, while delineation of residual anomaly map shows the nose structures occurs on Cilamaya-Karawang high. Locally, the gas fields of Jatirangon and Cicauh areas exist on the flank of the nose structure of Pangkalan-Bekasi High, while the oil/gas field of Northern Cilamaya is situated on the flank of the nose structure of Cilamaya-Karawang High. The concept of fluid/gas migration concentrated on nose structures which are delineated from gravity data can be applied in the studied area. This concept needs to be tested in other oil and gas field areas.